Desain Senyawa Turunan Karbamat Sebagai Insektisida Baru Menggunakan Metoda In Silico - Agus Dwi Ananto; Mudasir Mudasir; Ria Armunanto (Elkawnie, 2017)
Linear equation of QSAR model of insecticidal activity of carbamate derivatives based on atomic charge and hydrofobic, electronic and steric descriptors has been investigated. The descriptors were calculated by semiempirical PM3 method and biological activities of the compound were taken from experiment. The relationship between descriptors and their biological activities was analyzed with multilinear regression analysis.The best linier equation resulted from that analysis is : Log 1/LD 50 = 12,651 + (2,467 qC2) + (2,832 qC4) - (14,089 qC6) - (0,24 qO7) + (0,293 Î¼) - (0,08 SA (grid)) +(0,041 V)+ (0,141 EH) - (0,303 log P) n = 39 ; r = 0,839 ; adjusted r2 = 0,612 ; SE = 0,355; Fhit/Ftable = 3,443 PRESS=5,188 Based on that model, a new carbamate derivative has been designed which show better predicted activity (log 1/LD50 = 9,79) while the old one (log 1/LD50 = 8,81). This new carbamate insecticide derivative can be synthesized laboratoriccally for the next prove. Key Word:QSAR, Insecticides carbamate, PM3.